Desain Geometrik dan Tebal Perkerasan Lentur Rapid Exit Taxiway Middle 6 Bandar Udara Internasional Soekarno-Hatta dengan Metode FAA - Suse Lamtiar; Wahyu Dwi Agustini; Reza Pahlevi; Zhabri Gaffari D. (Politeknik Penerbangan Makassar, 2023)
Soekarno-Hatta International Airport is the busiest airport in Indonesia, in 2018 Soekarno-Hatta Airport was ranked the 17th busiest airport in the world with 462,071 aircraft movements per year, during peak hours Soekarno-Hatta International Airport served 100 aircraft movements per hour, the flight growth rate at Soekarno-Hatta International Airport is 7% per year (Rosalinda Avelina, 2018). According to (Tengku Annisa, 2016) the estimated peak hour obtained for 2020 is 148 movements, while in simulation calculations using the time-space analysis method the movements that can be served are 124 movements per hour. So it is known that there is a delayed of 24 movements. Based on the, the land on the south side of runway 06/24 Soekarno-Hatta International Airport can be made a rapid exit taxiway in the Middle 6 area. Therefore, the author plans a rapid exit taxiway by forecasting aircraft movements for 10 years The future uses the FAA (Federal Aviation Administration) method to serve delayed aircraft movements and reduce the waiting time for queues to enter the runway, so that the queue time to enter the runway is faster and reduces traffic congestion on the runway.